Early social environment and the fighting behaviour of young Oreochromis niloticus (Pisces, Cichlidae) - Barki, A.; Volpato, G. L. (Brill Academic Publishers, 1998)
This study examines the influence of early experience with different forms of aggressive behaviour on the fighting behaviour of young fish. Fry of the cichlid fish, Oreochromis niloticus, were raised from hatching in small groups consisting of a normal individual (the test fish) and either mutant conspecifics lacking the dorsal fin and thereby the ability to perform fin displays, or normal ones. Following a 63-day period of development in groups the test fish were confronted in their home tanks with an unfamiliar normal fish for 10 min. The fighting behaviour of the test fish was analyzed considering their previous group type (mutant or normal) and rank (alpha or beta). There was no difference between test fish in the rate and sequence of behaviour patterns used in fighting. However, test fish that had developed in mutant groups were rarely the first to bite in contests and had a longer latency to biting following the first bite of the stimulus fish than rest fish with normal experience. This finding is attributable to the form of aggressive behaviour experienced by the test fish during development but not to existing differences in the amount of aggression previously experienced, nor to previous rank, sex, or size relative to the stimulus fish. The results suggest that early experience influenced decision making by the test fish during the fight. The involvement of the fin displays and the possible mechanism of this influence are discussed.
Keywords: cichlid fish; Oreochromis niloticus; early experience; fighting behaviour